DESIGN OF A 12-STORY HIGH-RISE OFFICE BUILDING IN LOS ANGELES, CALIFORNIA, USA. - Seitkaliyev, Alibi; Amantay, Amirmagruf; Zhubanysh, Tangguli; Aidaraliyev, Bekbarys; Gabit, Aruzhan; Sissenova, Malika (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This paper proposes designing and constructing a 12-story office building at 940 N Sycamore Avenue in Los Angeles, California. The architectural design of the building aligns with the list of building codes, namely International Building Code (IBC), California Building Code (CBC), Los Angeles Municipal Code (LAMC), and California Building Standards Code (CBSC). The structural part aligns with the American Society of Civil Engineers (ASCE) guidelines. SAP 2000 software was used for the structural analysis of the building. Reinforced concrete is chosen as the main construction material due to its accessibility and cost-effectiveness. After preparing the soil profile of the site, Mat and Pile foundations were designed. We choose a group pile foundation due to its ability to support high loads. Moreover, calculations showed that settlement of a group of piles is significantly lower than settlement of mat foundation.
Keywords: Office building; Los Angeles; architectural design; structural design; materials; geotechnical analysis; type of access: open access